Influence of doxapram and intermittent 10% carbon dioxide inspiration on cardiovascular and laryngeal functions in anesthetized dogs. Issue 7 (5th August 2021) - Sakai, Daniel M.; Howard, Shenise L.; Reed, Rachel A.; Quandt, Jane E.; Barletta, Michele; Wallace, Mandy L.; Grimes, Janet A.; Schmiedt, Chad W.
Abstract: Objective: To compare the effects of two doses of doxapram intravenous injection and carbon dioxide inhalation on the cardiovascular and laryngeal functions of anesthetized hounds. Study Design: Experimental study. Animals: Six healthy adult dogs. Methods: In a Latin‐square design, the mean arterial blood pressure (MABP) and heart rate (HR) were recorded continuously. The inspiratory normalized glottic gap areas (iNGGA) were measured before and after each stimulation with 0.55 mg/kg of doxapram (L‐DOX), 2.2 mg/kg of doxapram (H‐DOX), or 90 s of inhalation of 10% carbon dioxide in oxygen (I‐CO2 ). The stimulations were tested in duplicate or triplicate. Video clips of the laryngeal movement were scored by board‐certified surgeons masked to the treatment. Results: The MABP increased with L‐DOX and H‐DOX up to 81% (both p < .001 compared to I‐CO2 ), and persisted during the other stimulations (both p < .001). An intermittent tachycardic effect of up to 79% increase in HR was observed with doxapram. The HR following H‐DOX was higher than L‐DOX and I‐CO2 (both p < .016). Neither hypertension nor tachycardia was observed with I‐CO2 . The iNGGA increased with all treatments ( p < .001). The iNGGA was greater with H‐DOX than L‐DOX and I‐CO2 (both p < .007). All treatments received higher scores (all p < .001) with acceptable inter‐ and intra‐observers Krippendorff's alphas. Conclusion: All treatments were effective respiratory stimulants in anesthetized dogs; however, doxapram caused hypertension and tachycardia. Clinical Significance: Carbon dioxide inhalation might improve arytenoid motion without cardiovascular effects in dogs during clinical airway examinations.